2009
DOI: 10.1016/j.cell.2009.08.020
|View full text |Cite
|
Sign up to set email alerts
|

A Vertebrate Polycomb Response Element Governs Segmentation of the Posterior Hindbrain

Abstract: Chromatin remodeling by Polycomb group (PcG) and trithorax group (trxG) proteins regulates gene expression in all metazoans. Two major complexes, Polycomb repressive complexes 1 and 2 (PRC1 and PRC2), are thought to mediate PcG-dependent repression in flies and mammals. In Drosophila, PcG/trxG protein complexes are recruited by PcG/trxG response elements (PREs). However, it has been unclear how PcG/trxG are recruited in vertebrates. Here we have identified a vertebrate PRE, PRE-kr, that regulates expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
168
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(172 citation statements)
references
References 71 publications
1
168
1
1
Order By: Relevance
“…42). In the rhombomere, the expression of MafB is regulated by a concentration gradient of retinoic acid 43,44 , indicating that the Mafb gene is a downstream target of the retinoic acid receptor, which dimerizes with RXR in the hindbrain. Furthermore, MafB is expressed in neural cells, podocytes in the kidney and the lens of the eye 26,45 .…”
Section: Discussionmentioning
confidence: 99%
“…42). In the rhombomere, the expression of MafB is regulated by a concentration gradient of retinoic acid 43,44 , indicating that the Mafb gene is a downstream target of the retinoic acid receptor, which dimerizes with RXR in the hindbrain. Furthermore, MafB is expressed in neural cells, podocytes in the kidney and the lens of the eye 26,45 .…”
Section: Discussionmentioning
confidence: 99%
“…However, one important and not fully addressed question is the mechanism by which chromatin modifiers set up such modification patterns. Because of the critical role of Polycomb response elements in recruiting the Polycomb group proteins in Drosophila (63,64), and because there are only a few Polycomb response elements identified in mammals (65,66), alternative recruitment mechanisms, such as non-coding RNA-mediated PRC2 recruitment have been proposed and debated (67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Polycomb-repressive complexes mediate chromatin compaction in flies and mice (Grau et al, 2011). This largescale chromatin change represses the expression of many developmental genes (Isono et al, 2005;Boyer et al, 2006;Lee et al, 2006;Lanzuolo et al, 2007;Sing et al, 2009). Another group of proteins, the GATA factors, regulate the conformation of chromatin, influencing gene expression (Vakoc et al, 2005).…”
Section: The Unknown Spatial Distribution Of Cis-regulatory Informationmentioning
confidence: 99%